Fishing Hooks: A Review - Thomas, Saly N.; Edappazham, Gipson; B., Meenakumari; P.M., Ashraf (Fishery Technology, 2025)
Fishing hooks stand out among the simplest and the oldest of such devices. They are not well studied, and the available studies are out dated due to emergence of new models materials and technologies. Methods of numbering of hooks are not standardized. This review dwells into their history and evolution, terminology, properties, classification, numbering, testing procedure and hooking efficiency. The study points to the need for a comparative study of hooks in terms of their relative properties and also as a conservation tool for sustainable development of recreational fishing